2013
DOI: 10.11613/bm.2013.042
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bone mineral density in patients on haemodialysis or peritoneal dialysis – a cross-sectional, longitudinal study

Abstract: Introduction:The aim of the study was to identify biomarkers of alteration in bone mineral density (BMD) in patients on haemodialysis (HD) and peritoneal dialysis (PD).Materials and methods:In a cross-sectional, longitudinal study dual-energy X-ray absorptiometry scans were performed in 146 HD-patients and 28 PD-patients. Follow-up after 14 months (mean) was conducted in 73 patients. As potential biomarkers we investigated parathyroid hormone (PTH), 25-hydroxy vitamin-D, ionised calcium, albumin, phosphate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
(35 reference statements)
4
5
0
Order By: Relevance
“…Several studies are consistent with our study showing that BMD decreased as age increased [14,17,18]. The effect of gender on bone mass in hemodialysis is controversial [19,20]. We found that BMD was significantly lower in women at the total body.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies are consistent with our study showing that BMD decreased as age increased [14,17,18]. The effect of gender on bone mass in hemodialysis is controversial [19,20]. We found that BMD was significantly lower in women at the total body.…”
Section: Discussionsupporting
confidence: 92%
“…No differences were found in BMD between hemodialysis and peritoneal dialysis [17]. Low BMD also represents an independent mortality risk factor [18].…”
Section: Introductionmentioning
confidence: 88%
“…Lastly, although our studies demonstrated an association between HD status and the higher risk of hip fracture, data on BMD among ESRD patients in included studies were limited. In addition, current evidence on the benefits of interventions to improve BMD on the improvement of fracture rates in ESRD patients remains controversial . However, the findings of our study highlight the need for future studies on the prevention of hip fractures among ESRD patients undergoing HD.…”
Section: Discussionmentioning
confidence: 79%
“…It is unclear if the difference in dialysis modality influences the hip fracture risk among ESRD patients and, if so, which modality has less risk. Each dialysis modality causes physiological changes that may affect the bone and mineral metabolism differently . The choice of renal replacement therapy usually depends on several important factors.…”
Section: Introductionmentioning
confidence: 99%